THE ROLE OF THE MOSQUE IN ESTABLISHING PEACE OF COMMUNITY AFFECTED BY DISASTER AFFECTS (CASE STUDY OF MOSQUES IN PALU CITY) - Muhsin Muhsin (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
This paper wants to show that mosques can help peace of mind for people affected by disasters. Many people who are affected by disasters, especially Muslims, when natural disasters occur, many run to the mosque. This phenomenon is very worthy of research and this happened in the city of Palu. In this study the author has also compared several other works with the author's writings including, first, Muhadi's work with the title Mosque as a Da'wah Center, and secondly Nurul Jannah's work with the title Revitalizing the Role of Mosques in the Modern Era (Case Study of Medan City), third, there is also M Syafi's work entitled Building Mosques at the Time of the Prophet and Its Implications for Women's Mosque Congregations, Fourth Mosque-Based Community Education by Suhairi Umar and fifth a journal article entitled "Mosques in the Trajectory of Islamic History" by Syamsul Kurniawan. These five works both explain about mosques, but there are several aspects that are examined differently, namely the object of this research study is the people who live in the area around the mosque whether they are calm or not, while the three works do not explain this. While the method used is descriptive analysis by using this method researchers will collect data based on the results of interviews with researchers. Based on the results of this study, the mosque is able to provide peace of mind due to the closeness of a human being with his god, when in the mosque a human feels that God or the Khaliq is near him, causing him to feel calm. This also happened in the city of Palu, when an earthquake occurred, some people ran to the mosque. Tulisan ini ingin menunjukkan bahwa masjid dapat membantu ketenangan jiwa bagi masyarakat yang terkena bencana. Banyak masyarakat yang terkena bencana khususnya umat Islam, ketika terjadi peristiwa bencana alam banyak yang berlarian ke masjid. Fenomena ini sangat layak untuk diteliti dan ini terjadi di kota Palu. Dalam penelitian ini penulis juga telah membandingkan dengan beberapa karya yang lain denan tulisan penulis diantaranya, pertama, karya Muhadi dengan judul Masjid sebagai Pusat Dakwah, dan kedua karya Nurul Jannah dengan judul Revitalisasi Peranan Masjid di Era Modern (Studi Kasus Kota Medan), ketiga, terdapat pula karya M Syafi yang berjudul Bangunan Masjid Pada Masa Nabi dan Implikasinya Terhadap Jamaah Masjid Perempuan, Keempat Pendidikan Masyarakat Berbasis Masjid oleh Suhairi Umar dan kelima sebuah artikel jurnal yang berjudul “Masjid Dalam Lintasan Sejarah Umat Islam” oleh Syamsul Kurniawan. Lima karya ini sama-sama menjelaskan tentang masjid, akan tetapi ada beberapa aspek yang diteliti berbeda yaitu objek kajian penelitian ini adalah masyarakat yang tinggal di daerah sekitar masjid apakah tenang atau tidak, sedangkan tiga karya tersebut tidak menjelaskan hal tersebut. Sedangkan metodo yang digunakan adalah analitis deskriptif dengan menggunakan metode ini peneliti akan mengumpulkan data berdasarkan hasil wawancara peneliti. Berdasarkan hasil dari penelitian ini yaitu masjid mampu memberikan ketenangan jiwa disebabkan kedekatan seorang manusia dengan tuhannya, ketika di masjid seorang manusia merasa bahwa Tuhan atau sang Khaliq berada di dekat dia, sehingga menyebabkan dia merasa tenang. Hal ini terjadi pula di kota Palu, ketika terjadi gempa maka sebagian masyarakat lari ke masjid.